2016
DOI: 10.1155/2016/8364279
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl-L-cysteine Protects the Enterocyte against Oxidative Damage by Modulation of Mitochondrial Function

Abstract: The neonatal small intestine is susceptible to damage caused by oxidative stress. This study aimed to evaluate the protective role of antioxidant N-acetylcysteine (NAC) in intestinal epithelial cells against oxidative damage induced by H2O2. IPEC-J2 cells were cultured in DMEM-H with NAC and H2O2. After 2-day incubation, IPEC-J2 cells were collected for analysis of DNA synthesis, antioxidation capacity, mitochondrial respiration, and cell apoptosis. The results showed that H2O2 significantly decreased (P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Contrary to the result of LPS challenge, NAC had no effect on intestinal function including cytokine expression, intestinal barrier function, and intestinal wound healing in NAC treatment without LPS challenge in IPEC-J2 cells. In agreement with the present study, it has been reported that only cell proliferation, mitochondrial respiration, lactate dehydrogenase concentration, and apoptosis were not affected by NAC in small intestinal epithelial cells 34 . The function of NAC might be inadequate, but it can be effective in special condition such as inflammation.…”
Section: Discussionsupporting
confidence: 94%
“…Contrary to the result of LPS challenge, NAC had no effect on intestinal function including cytokine expression, intestinal barrier function, and intestinal wound healing in NAC treatment without LPS challenge in IPEC-J2 cells. In agreement with the present study, it has been reported that only cell proliferation, mitochondrial respiration, lactate dehydrogenase concentration, and apoptosis were not affected by NAC in small intestinal epithelial cells 34 . The function of NAC might be inadequate, but it can be effective in special condition such as inflammation.…”
Section: Discussionsupporting
confidence: 94%
“…Previous work has also shown that NAC has beneficial effects on mitochondrial function through increased synthesis of pyruvate dehydrogenase, a key enzyme for mitochondrial energy metabolism, in the mouse liver in vivo (Zwingmann & Bilodeau, ) and elevated rates of mitochondrial respiration in porcine intestinal epithelial cells in vitro (Xiao et al . ). In this study, we demonstrate that acute treatment with NAC effectively increased the litter size and viable fetal number in DHT+insulin‐treated pregnant rats, thus supporting its therapeutic potential for reducing ROS‐mediated fetal loss under PCOS conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Although it is beyond the scope of functional amino acids, several indispensable amino acids, such as tryptophan and sulfur amino acids, have also attracted large attention recently (108110). A growing evidence has revealed that supplementation of these amino acids beyond the current NRC requirement brought positive effects on intestinal health of weaned pigs by regulating host physiology, metabolism, oxidative status, and immunity (108110). The modification of gut microbiota and their metabolites by these amino acids was also highly correlated to the enhanced gut barrier functions of weaned pigs (109).…”
Section: Nutritional Intervention On Intestinal Development and Healtmentioning
confidence: 99%